1986
DOI: 10.1111/j.2044-8341.1986.tb02659.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the object focus of therapist interpretations and outcome in short‐term individual psychotherapy

Abstract: The relationships between the object (person) focus of therapist interpretations and outcome were examined for 21 patients who received short-term individual psychotherapy. Percentages of single objects and linked objects, e.g. therapist-parent link, were derived from an analysis of the therapy sessions. Patients, therapists and an independent assessor provided pre-therapy, post-therapy and six-month follow-up outcome scores. Contrary to other reports in the literature little evidence was found to support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 1 publication
(1 reference statement)
2
33
0
2
Order By: Relevance
“…In an early study reviewing therapist notes recalled by the therapist after sessions, Malan (1976) reported a positive correlation between interpretations that linked the patient's relationship to the therapist to that of the patient's parents ('transference parent linking interpretations') and positive out come, a finding replicated by Marziali (1984) in a study of audiotaped sessions. However, Piper et al (1986) found that transference interpretations were uncorrelated with outcome. Furthermore, Rosser et al (1983), in a study of 32 patients with respiratory disease randomised to eight sessions of psycho analytic psychotherapy in which the analyst was instructed either to make free use of transference interpretations or to withhold such inter pretations, found that change in psychiatric symp toms was significantly greater in the latter group.…”
Section: Transferencementioning
confidence: 93%
“…In an early study reviewing therapist notes recalled by the therapist after sessions, Malan (1976) reported a positive correlation between interpretations that linked the patient's relationship to the therapist to that of the patient's parents ('transference parent linking interpretations') and positive out come, a finding replicated by Marziali (1984) in a study of audiotaped sessions. However, Piper et al (1986) found that transference interpretations were uncorrelated with outcome. Furthermore, Rosser et al (1983), in a study of 32 patients with respiratory disease randomised to eight sessions of psycho analytic psychotherapy in which the analyst was instructed either to make free use of transference interpretations or to withhold such inter pretations, found that change in psychiatric symp toms was significantly greater in the latter group.…”
Section: Transferencementioning
confidence: 93%
“…The Plan provided us with a standard-a ruler-against which the therapist's interventions could be compared to evaluate the goodness-of-fit of each intervention for each particular patient. Recently, researchers from other theoretical orientations have focused on developing their own instruments for including the variable of accuracy of interpretations (Crits-Christoph, Cooper, Crits-Christoph, Luborsky, Dahl, Popp, Mellon, & Mark, 1988); some have focused on the categories of interpretations (Piper, Azim, Joyce, & McCallum, 1991;Piper, Debbane, Bienvenu, de Carufel, & Garant, 1986;Piper, Debbane, de Carufel, & Bienvenu, 1987); some have investigated both (Fried, Crits-Christoph, & Luborsky, 1992;Crits-Christoph, Demorest, & Connolly, 1990;Horowitz, 1987;1991;Luborsky & Crits-Christoph, 1990;Luborsky, Crits-Christoph, & Mellon, 1986;Perry, 1989;Perry, Luborsky, Silberschatz, & Popp, 1989;Strupp & Binder, 1984).…”
mentioning
confidence: 98%
“…To fill this void, for our meta-analytic review we aggregated studies in which therapist adherence or competence was examined in relation to outcome. As we discuss later in more detail, in addition to including studies in which the relation between ratings of entire adherence or competence scales and outcome were examined, we also included studies that assessed only particular components of adherence or competence that were believed to be especially important to the treatment modality in question on the basis of either prior empirical evidence or theory (e.g., Intrapersonal Consequences subscale of the Coding System of Therapist Feedback [CSTF] for Castonguay, Goldfried, Wiser, Raue, & Hayes, 1996; various measures assessing therapist interpretations in dynamic therapy for Crits-Christoph, Cooper, & Luborsky, 1988; Marziali, 1984; Piper, Azim, Joyce, & McCallum, 1991; Piper, Debbane, Bienvenu, de Carufel, & Garant, 1986; the Errors in Technique subscale of the Vanderbilt Negative Indicators Scale [VNIS] for Sachs, 1983; Cognitive Therapy–Concrete subscale of the CSPRS for Webb et al, 2009). …”
mentioning
confidence: 99%